Effect of Lead, Cadmium, and Continuous Exposure to Heat as an Occupation Hazards on Fertility in Male Workers - Algafari, Rebah N; Ramadhan, Rehab S; Al-Jeboury, Ghyda'a H (Al-Nahrain Journal of Science, 2011)
In this work, sample of workers who are in contact with heavy metals were selected. Those were distributed as follow car customizers and welders (CW) (25), bakers (20) local power generator operators “operators” (15), and control men who their occupation was far from such contact (20). The study included measurement of testosterone, LH and FSH as fertility hormones, measurement of lead and cadmium (Cd) as heavy metals, and exposure to heat during the working day. Results showed that fertility hormones were within the control levels in all subjects; only a significant increase (p≤0.05) was recorded in LH in (CW) compared with control. Seminal fluid analysis (SFA), showed a decrease in total sperm count in all samples when compared with control. No significant raise was found in heavy metals in bakers, while a significant elevation of both types of heavy metals were recorded in blood of (CW) and (operators). It is concluded that occupation might result in elevating levels of heavy metals in welders and car customizers, and local power generator operators